Perancangan Sistem Kartu Indentitas Berobat Elektronik Menggunakan Visual Studio 2010 Di RSUD Lembang - Kurniawan, Asep; Waluyo, Marcel Pesa Dwi; Ulfah, Annisa; Abdussalaam, Falaah (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Technology and computerization in hospitals are very important, to improve health services. Hospitals need changes in the registration section where in Lembang Hospital there are still frequent delays in service due to the treatment identity cards owned by patients are easily damaged or faded because they are still handwritten on paper cards, this study aims to make the electronic medical identity card system a a card made from vpc which is not easily damaged and this can help to improve services at the Lembang Hospital. This research method uses a qualitative method with a descriptive approach which is carried out by observation, interviews, literature studies and system development methods using the SLDC method. The tools used are in the form of DFD diagrams and programming using Visual Studio 2010. Sowith this system, it is hoped that the quality of service will increase because patients can store medical identity cards safely and medical record officers can easily find patient data on the system.